Uma arquitetura para integração de processos de negócio e processamento de situações contextuais - Rohten, Luis Augusto Melo (2019)
In recent years, the concept of situation-awareness has been exploited by organizations, allowing their information systems to work with context-sensitive data. These systems seek to detect a particular state of interest in reality, i.e., a contextual situation, and react accordingly, thus contributing to improve business adaptability to changes in domain conditions. In this work, we describe a conceptual architecture focused on the representation of contextual situations through business rules, and their integration with business processes. As a proof of concept, an empirical experiment was leaded to validate the proposal. The work developed showed that bringing situation-awareness to information systems can reduce the complexity of business processes, as well as increase the reliability of the domain representation model.